2000
DOI: 10.1002/1097-0223(200010)20:10<838::aid-pd911>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

High levels of fetal erythroblasts and fetal extracellular DNA in the peripheral blood of a pregnant woman with idiopathic polyhydramnios: case report

Abstract: Abnormal amniotic fluid volume can be associated with increased maternal risk as well as perinatal morbidity and mortality. Polyhydramnios is often indicative of fetal, placental or maternal problems. In a large proportion of patients the aetiology of the disorder is unclear. Here we report on a case in which numerous fetal erythroblasts and large quantities of extracellular fetal DNA were found in the peripheral blood of a pregnant woman with idiopathic polyhydramnios bearing a male fetus. Following enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 13 publications
0
32
0
3
Order By: Relevance
“…Increased concentration of fetal DNA was identified in different obstetrical conditions (preeclampsia, preterm delivery, fetal-maternal hemorrhage, polyhydramnios etc.) but also in trisomy 21 (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentration of fetal DNA was identified in different obstetrical conditions (preeclampsia, preterm delivery, fetal-maternal hemorrhage, polyhydramnios etc.) but also in trisomy 21 (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that circulating fetal DNA concentrations in maternal plasma are increased in pregnancies affected by preeclampsia (6,7 ), fetal growth restriction (8 ), or preterm labor (9 ); pregnancies with aneuploid fetuses (10,11 ); and pregnancies affected by other pregnancy-related disorders involving an underlying placental pathology (12,13 ). This has led to the suggestion that abnormalities in placentation may be associated with increased liberation of fetal DNA into the maternal circulation (14,15 ).…”
mentioning
confidence: 99%
“…Fetal rhesus D genotyping from maternal plasma (10 ) is a routinely used protocol for prenatal diagnosis in several centers. Increased fetal DNA concentrations have been observed in the blood of women with various complications of pregnancy, including preeclampsia (11)(12)(13)(14)(15)(16).…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%